2005
DOI: 10.1063/1.1871246
|View full text |Cite
|
Sign up to set email alerts
|

Review of progress in Fast Ignition

Abstract: Marshall Rosenbluth's extensive contributions included seminal analysis of the physics of the laser-plasma interaction and review and advocacy of the inertial fusion program. Over the last decade he avidly followed the efforts of many scientists around the world who have studied Fast Ignition, an alternate form of inertial fusion. In this scheme, the fuel is first compressed by a conventional inertial confinement fusion driver and then ignited by a short ͑ϳ10 ps͒ pulse, high-power laser. Due to technological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
79
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(80 citation statements)
references
References 33 publications
1
79
0
Order By: Relevance
“…This implies that the product of B / L / needs to be larger than the fast electron momentum to reflect the fast electrons back towards the guide axis. The resistive guide has been suggested for applications such as the Fast Ignition approach to the inertial confinement fusion scheme 6,7 where the energetic fast electrons need to be guided through an overdense stand-off distance of 100 lm or more 8 and deposited into the compressed core of deuterium-tritium (DT) plasma. It has been suggested that a resistive guide element can also be used as a driver in hydrodynamic experiments 4,9 since strong heating occurs where the fast electron beam is collimated.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the product of B / L / needs to be larger than the fast electron momentum to reflect the fast electrons back towards the guide axis. The resistive guide has been suggested for applications such as the Fast Ignition approach to the inertial confinement fusion scheme 6,7 where the energetic fast electrons need to be guided through an overdense stand-off distance of 100 lm or more 8 and deposited into the compressed core of deuterium-tritium (DT) plasma. It has been suggested that a resistive guide element can also be used as a driver in hydrodynamic experiments 4,9 since strong heating occurs where the fast electron beam is collimated.…”
Section: Introductionmentioning
confidence: 99%
“…Recent improvements in particle energy spread [6] may allow compact laser-based radiation sources to be useful someday for cancer hadrontherapy [7] and as injectors into conventional accelerators [8], which are critical tools for x-ray and nuclear physics research. They might also be used for "fast ignition" [9] of inertial fusion targets. The ultrashort pulse duration of these particle bursts and the x rays they can produce, hold great promise as well to resolve chemical, biological or physical reactions on ultrafast time scales and on the spatial scale of atoms [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have intensively been performed since this proposal [2,3]. In Japan, the FIREX-I project [4] has been started for the sake of heating the core up to the temperature of 5 keV.…”
Section: Introductionmentioning
confidence: 99%